2022
DOI: 10.1186/s12920-022-01335-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel CREBBP mutation and its phenotype in a case of Rubinstein–Taybi syndrome

Abstract: Background This study was to report a novel CREBBP mutation and phenotype in a child with Rubinstein–Taybi syndrome. Methods Case report of a 9-year-old boy. Results We described the patient’s clinical manifestations in detail, and found that in addition to the typical systemic manifestations of the syndrome, the outstanding manifestation of the child was severe intellectual deficiency and prominent oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…The CREBBP gene influences CREB-binding proteins that play a role in regulating the activity of various genes in tissues throughout the body ( Cardinaux et al, 2000 ; Gao et al, 2020 ). Previous studies have shown that the CREBBP-binding proteins are involved in brain development and long-term memory formation ( Chatterjee et al, 2020 ; Wang et al, 2022 ). CREBBP gene may play a role in the pathogenesis of various neurodegenerative diseases, such as HD ( Steffan et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CREBBP gene influences CREB-binding proteins that play a role in regulating the activity of various genes in tissues throughout the body ( Cardinaux et al, 2000 ; Gao et al, 2020 ). Previous studies have shown that the CREBBP-binding proteins are involved in brain development and long-term memory formation ( Chatterjee et al, 2020 ; Wang et al, 2022 ). CREBBP gene may play a role in the pathogenesis of various neurodegenerative diseases, such as HD ( Steffan et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The hereditary condition RSTS is linked to mutations in CREBBP and is characterized by ID and developmental delays. 14 The mutations detected in RSTS patients range from point mutations to microdeletions eliminating the entire gene, leading to the haploinsufficiency of this dosage-sensitive gene. 15 More specifically, studies of individuals with missense and splice-site mutations in the CREBBP HAT domain revealed that loss of HAT activity is sufficient to cause the ID syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a role in complexes that remodel chromatin, affects development, and aids in the control of genes through epigenetic mechanisms 12,13 . The hereditary condition RSTS is linked to mutations in CREBBP and is characterized by ID and developmental delays 14 . The mutations detected in RSTS patients range from point mutations to microdeletions eliminating the entire gene, leading to the haploinsufficiency of this dosage‐sensitive gene 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a reasonable and effective assessment of managing financial risks and studying risk linkages and spillover effects among financial markets are beneficial for regulators to track and control the risks of each financial market in a timely manner [6][7][8][9]. This allows a better grasp of the direction of financial risks and is important for promoting stable and healthy economic development [10][11][12][13][14]. Therefore, in the context of globalization, how to effectively assess and manage risks is gradually drawing the attention of financial market regulators and practitioners [15].…”
Section: Introductionmentioning
confidence: 99%